The Effects of a Structured Yoga Intervention on Cognitive, Psychological, and Functional Performance in Competitive Women’s Basketball Players: A Two-Group Controlled Experimental Study - Vijayalakshmi C; Saroja S (Physical Education Theory and Methodology, 2025)
Background. Yoga has received a lot of focus as a holistic training method combining physical, psychological, and cognitive development, although there is still a lack of controlled evidence in women’s competitive team sports. Objectives. This study aimed to evaluate the impact of an eight-week structured yoga intervention on cognitive focus, psychological resilience, perceived stress, and functional performance of collegiate women’s basketball players. Materials and Methods. A total of thirty athletes (aged 19-24 years) were randomly divided into an Experimental Group (yoga + routine training) and a Control Group (routine training only). Cognitive (d₂ Test of Attention), psychological (CD-RISC-10, PSS-10), and physical (vertical jump, sprint, agility) outcomes were assessed before and after the intervention. Data analysis was performed using mixed ANOVA and confirmatory ANCOVA with baseline covariates. Effect sizes (Cohen’s d, partial η²), along with 95% confidence intervals, were calculated, and the p-values were adjusted according to the Benjamini-Hochberg false discovery rate (FDR) method. Results. For cognitive focus (p < .001), resilience (p = .004), stress reduction (p = .002), and agility (p = .011), significant Group × Time interactions were noted. ANCOVA verified the strength of these effects, even after controlling for differences in baseline. PCA revealed two latent dimensions, namely psychological-cognitive and motor performance,which together accounted for more than 75 % of the variance. Conclusions. The yoga program markedly improved psychophysiological readiness and functional efficiency in comparison to routine training. These findings suggest that yoga can be an integrative approach for enhancing athletes’performance at the preparation stage.